Findings of Reduced Head Circumference with COVID-19 Infection in the Third Trimester: A Retrospective Cohort Study - Kristen Lee Moriarty; Kelsey Manfredi; Pascale Carrel; Emma Kryzanski; David A. Schwartz; Lucas Godoy; Chia-Ling Kuo; Andrea Shields (Biomedicines)
Background: COVID-19 is linked to multiple adverse pregnancy outcomes but with inconsistent evidence associating the disease with fetal growth restriction (FGR) and small for gestational age (SGA). There are limited data on the impact of COVID-19 on neonatal growth measurements, specifically microcephaly without SGA or low birth weight. We hypothesize that COVID-19 is associated with smaller neonatal head measurements without increasing the risk of small for gestational age. This relationship may be related to the timing of COVID-19 exposure in pregnancy. Methods: An Institutional Review Board (IRB) approved retrospective cohort study enrolled 140 COVID-19-infected and 136 COVID-19-uninfected patients. Inclusion criteria: (a) singleton birth between 28 April 2020 and 31 December 2022; and (b) maternal COVID-19 infection diagnosed via polymerase chain reaction (PCR). Exclusion criteria: Less than 12 years of maternal age, major fetal anomalies, and fetal loss < 15 weeks. The outcomes were a comparison of newborn growth measurements (length, weight, and head circumference (HC) at birth), Ponderal Index (PI), and development of SGA between SARS-CoV-2-infected and uninfected patients. Maternal and neonatal characteristics were descriptively summarized, and multivariate analyses and linear regression models were performed. Baseline maternal demographics did not differ amongst cohorts. Results: Compared to the uninfected cohort, COVID-19 diagnosed in the third trimester was associated with a lower neonatal HC compared to newborns of uninfected patients (β = −0.38 [0.38 SD lower], 95% CI −0.65 to −0.10, p = 0.024). There was no significant difference among cohorts in birth length, weight, or diagnosis of small for gestational age. Conclusions: We found that COVID-19 infection in the third trimester was associated with a lower neonatal head circumference without associated SGA. The cause underlying this association is unknown. Further research to determine the risk of neurotropic fetal infection by SARS-CoV-2, like ZIKA’s effect on the fetal immune system leading to microcephaly, is urgently needed.